2016
DOI: 10.1515/amcs-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis and H control of discrete T–S fuzzy hyperbolic systems

Abstract: This paper focuses on the problem of constraint control for a class of discrete-time nonlinear systems. Firstly, a new discrete T-S fuzzy hyperbolic model is proposed to represent a class of discrete-time nonlinear systems. By means of the parallel distributed compensation (PDC) method, a novel asymptotic stabilizing control law with the "soft" constraint property is designed. The main advantage is that the proposed control method may achieve a small control amplitude. Secondly, for an uncertain discrete T-S f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Several sorts of conditions can be taken into account during the design stage (Tanaka and Wang, 2001): stability, decay rate, state and input constraints, H ∞ -norm, etc. Recently, some papers (Saifia et al, 2012;Chang and Shih, 2015;Nguyen et al, 2015;Klug et al, 2015;Duan et al, 2016;Vafamand et al, 2016) have reported research on designing fuzzy controllers for TS fuzzy models when perturbations are present and there exists actuator saturation and state 458 J.V. Salcedo et al Nguyen et al (2015; and Vafamand et al (2016) claim that they outperform previous results (Saifia et al, 2012;Chang and Shih, 2015;Klug et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Several sorts of conditions can be taken into account during the design stage (Tanaka and Wang, 2001): stability, decay rate, state and input constraints, H ∞ -norm, etc. Recently, some papers (Saifia et al, 2012;Chang and Shih, 2015;Nguyen et al, 2015;Klug et al, 2015;Duan et al, 2016;Vafamand et al, 2016) have reported research on designing fuzzy controllers for TS fuzzy models when perturbations are present and there exists actuator saturation and state 458 J.V. Salcedo et al Nguyen et al (2015; and Vafamand et al (2016) claim that they outperform previous results (Saifia et al, 2012;Chang and Shih, 2015;Klug et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Especially, for discrete-time T-S fuzzy systems, results devoted to SOF control can be found in [5,12,18,19,21,23,24]; and especially, in [4] and [12], where a fuzzy weighting-dependent Lyapunov function (FWDLF) has been used. At last, some performances are generally to be added, H ∞ attenuation being one of the most widely used for T-S systems [8,[10][11][12][13]17,19,20,22,[25][26][27][28][29][30]. For real-time control, another important issue is the physical limitations of the actuators, such as input bounds and/or rate saturation constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Many results are reported in the literature regarding stability analysis of linear (more recently, see [35][36][37][38]) and nonlinear systems [8,10,16,25,26,[31][32][33][34][40][41][42]45] subject to input constraints. Several approaches were experienced with T-S systems: bound on the initial conditions to avoid the input saturation in low gain control laws [16,26,40]; estimation of the attraction domain in the presence of actuator saturation [8,10,16,38,40,41,45]; transformation of the saturation into a dead-zone nonlinearity [8], use of a polytopic model to express the saturation constraints in [10,16,[20][21][22]25,26,[35][36][37][38][39][40][41]45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [45,46], to achieve small control amplitude, a new T-S fuzzy hyperbolic model was developed, moreover, Ref. [46] considered the input delay of the novel model.…”
Section: Introductionmentioning
confidence: 99%